Friability, Slacking Characteristics, Low-Temperature Carbonization Assay And Agglutinating Value Of Washington And Other Coals ? Introduction - H. F. Yancey (The National Institute for Occupational Safety and Health (NIOSH), 1932)
One of the important duties of the Bureau of Mines is to sample and analyze coals and to publish the results of such analyses for the information of producers, consumers, and the general public. Numerous publications containing such analyses have been Issued from time to time. Although the chemical properties of a coal as revealed by its proximate and/or ultimate analysis and heating value aid one considerably in visualizing its probable behavior and in determining its usefulness and value for a specific purpose, they do not furnish complete information. The physical properties of a coal, such as its ability to retain its original form without undue breakage or degradation in size under the various conditions of storage and usage, are also of importance in determining its suitability, technically or economically, for a given purpose.